Species Identification of Golden and Bald Eagle Talons Using Morphometrics - Appleton, Avery J.; O'Brien, R. Christopher; Trail, Pepper W. (Digital Commons @ New Haven, 2016)
The Golden Eagle (Aquila chrysaetos) and Bald Eagle (Haliaeetus leucocephalus) are the largest avian predators in North America, and are thus species of great ecological importance and cultural significance. There is a long history of human use of eagle body parts, and this use continues today: Bald and Golden eagles are among the North American birds most affected by the illegal wildlife trade. Detached eagle talons are often recovered in both law enforcement and archaeological contexts, but data to allow morphological identification of these talons have been lacking. This study documents measureable differences in the morphology of Bald Eagle and North American Golden Eagle talons, which can be used to identify the detached talons of these two species. We measured talon samples of both species from the U.S. Fish and Wildlife Service’s National Fish and Wildlife Forensics Laboratory and other collections and categorized them according to species, sex, age, and digit number (Digits I–IV). We then conducted ANOVA and principal components analysis to test for statistical differences in the talon measurements of these two species. Although species identification was not always possible, due to overlap in the morphology of the talons of the two eagles, our results demonstrated that measurements allow identification of many talons, especially the large talons of Digits I and II, which are most commonly recovered in law enforcement cases. These results will be valuable for researchers studying North American eagle remains in the contexts of law enforcement, archaeology, and anthropology.